The final exam - Daneshvari, Gitty; Gifford, Carrie (New York : Little, Brown and Company, 2012)
When a reporter plans an exposé that could shut down the School of Fear, Garrison, Lulu, Madeleine, Theo and Hyacinth seek help from Bishop Basmati, head of the nearby Contrary Conservatory, whose hyperactive, fearless, and extremely impulsive students soon overrun the School of Fearians.
Keywords: Phobias -- Juvenile fiction; Detective and mystery fiction